SELEKSI POHON INDUK JENIS MERANTI (Shorea spp) PADA AREAL TEGAKAN BENIH IUPHHK-HA PT. SUKA JAYA MAKMUR KABUPATEN KETAPANG - Samsul, .; Muin, Abdurrani; Burhanuddin, . (JURNAL HUTAN LESTARI, 2016)
Shorea is an important species in Asia. Shorea much use for the material in the timber industry in Indonesia. The study entitled "Parent Tree Selection Type Shorea In the area of ​​stands Seed IUPHHKHA PT. Suka Jaya Makmur Ketapang "aims to determine the number of Shorea trees that qualify as mother trees in the area of ​​seed stands PT. Suka Jaya Makmur, Ketapang. This research was conducted in the area of ​​seed stands IUPHHKHA PT. Suka Jaya Makmur Ketapang in West Kalimantan, using the method of exploration. Research results obtained nine trees that have either phenotype quality to serve as the parent tree. Key words: Parental tree, Parental tree criteria, Shorea.